2022
DOI: 10.1002/chem.202202897
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Dehydropolymerization of Phosphine–Boranes at Ambient Temperature

Abstract: Stoichiometric reaction of phosphine–borane adducts RR'PH⋅BH3 (R=Ph, R’=H, Ph, Et, and R=R’=tBu) with the strong acid HNTf2 (Tf=SO2CF3) leads to H2 elimination and the formation of the triflimido derivatives, RR'PH⋅BH2(NTf2). Subsequent deprotonation by using bases, such as diisopropylethylamine or the carbene IPr (IPr=N,N’‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene), led to the formation of P‐mono‐ or ‐disubstituted polyphosphinoboranes [RR'P‐BH2]n. Evidence for the intermediacy of transient phosphinoborane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Multiply bonded species involving elements of group 13 and 15 are of particular interest as a result of their isosteric relationship with carbon-based compounds such as olefins and acetylenes. , In addition, we and others have recently provided evidence that highly reactive transient aminoboranes (e.g., MeNHBH 2 ) and phosphinoboranes (e.g., t -BuPHBH 2 ) are key intermediates in the formation of polyaminoboranes and polyphosphinoboranes, respectively, which represent promising examples of functional main group polymers. Although diverse examples of isolable aminoboranes R 2 BNR′ 2 with BN double bonds and iminoboranes RBNR′ with BN triple bonds , are known, the corresponding phosphorus–boron chemistry is considerably less developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiply bonded species involving elements of group 13 and 15 are of particular interest as a result of their isosteric relationship with carbon-based compounds such as olefins and acetylenes. , In addition, we and others have recently provided evidence that highly reactive transient aminoboranes (e.g., MeNHBH 2 ) and phosphinoboranes (e.g., t -BuPHBH 2 ) are key intermediates in the formation of polyaminoboranes and polyphosphinoboranes, respectively, which represent promising examples of functional main group polymers. Although diverse examples of isolable aminoboranes R 2 BNR′ 2 with BN double bonds and iminoboranes RBNR′ with BN triple bonds , are known, the corresponding phosphorus–boron chemistry is considerably less developed.…”
mentioning
confidence: 99%
“…Recently, computational reports suggested that phosphaborenes can be stabilized by sufficiently sterically encumbering ligands . Given our interest in potentially reactive multiply bonded boron–phosphorus species, we sought to examine whether this hypothesis could be experimentally verified.…”
mentioning
confidence: 99%
“…Polyphosphinoborane homopolymers are generally (but not exclusively[ 21 , 22 , 23 , 24 ]) synthesized by the catalytic dehydropolymerization[ 25 , 26 ] of precursor primary phosphine–boranes, H 3 B ⋅ PRH 2 , where H 2 is the only by‐product (Scheme 2 A). While initial reports used melt conditions at temperatures of up to 130 °C with catalysts such as [Rh(COD)Cl] 2 , [27] more recently catalyst systems that operate in solution at lower temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphosphinoborane homopolymers are generally (but not exclusively [21][22][23][24] ) synthesized by the catalytic dehydropolymerization [25,26] of precursor primary phosphine-boranes, H 3 B • PRH 2 , where H 2 is the only byproduct (Scheme 2A). While initial reports used melt conditions at temperatures of up to 130 °C with catalysts such as [Rh(COD)Cl] 2 , [27] more recently catalyst systems that operate in solution at lower temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%